Soil organic matter as a nitrogen source for Brassica napus - Carter, Candace, author; Schipanski, Meagan, advisor; Fletcher, Richard, committee member; Vivanco, Jorge, committee member; Wallenstein, Matthew, committee member (Colorado State University. Libraries, 2020)
Decreasing nitrogen (N) fertilizer losses from agricultural systems is a major focus in sustainable agriculture research. Most research to date has focused on reducing and managing N fertilizer additions in time and space. However, approximately half of the N taken up by most field crops is not from that season's fertilizer but is derived from the mineralization of soil organic matter (SOM). Despite its importance, intentionally managing crop utilization of background SOM as a source of N has received little attention. Our study explored N uptake patterns of rapeseed or canola (Brassica napus) in a greenhouse pot study and in a field setting. In the greenhouse pot study, we explored the effects of rapeseed genotypic diversity on N uptake from organic and inorganic N sources. We used dual 15N labeled ammonium-nitrate fertilizer to examine N uptake patterns of rapeseed in different N environments. Using a full factorial experiment, 10 varieties were grown under four treatments that included combinations of high and low N fertilizer and SOM. While we found limited varietal differences in N uptake dynamics, SOM was an important N source across all varieties even as N fertilizer availability increased. Our High SOM/High Fertilizer treatment obtained 64% of N from SOM, while the High SOM/Low Fertilizer obtained 89% of total N from SOM. Nitrogen source uptake was dependent on the treatment level N availability. We found evidence of enhanced SOM mineralization in higher N treatments, where high N fertilizer additions increased overall plant N uptake from SOM by 42% relative to low N fertilizer treatments. Although overall plant N uptake from SOM increased in high fertilizer treatments, microbial enzyme activity related to nutrient mineralization processes was suppressed in the high N fertilizer treatments relative to low fertilizer treatments in similar SOM environments by 16-58%. This result suggests high N fertilizer additions change microbial nutrient cycling dynamics. Based on the general results from our greenhouse study that N from SOM had an additive effect to fertilizer additions on rapeseed biomass production, we estimated the potential yield contributions of SOM increases with the adoption of conservation tillage practices in Canada. We used yield data provided by a literature search and the Canola Council of Canada to examine how the adoption of conservation tillage practices over the last 25 years has contributed to crop yield improvements in the Canadian prairies. We found that on average canola yields increase by 54.9 kg/ha per year, with 13% of annual yields attributed to agronomic practices. We estimated that the adoption of conservation tillage has increased soil N by 320 kg N/ha per year. Although N mineralization is highly variable and dependent on many factors, we estimated that 2% of total soil N is available annually for plant uptake. This translated to an additional 6.4 kg N/ha per year available for plant nutrition. We estimated that 91 to 164 kg/ha of the annual canola yield increases could be contributed to an increase in soil N availability. It is important to acknowledge the complex nature of N mineralization and plant N uptake patterns. This complexity likely leads to an underestimation of the contribution of SOM as an N source in cropping systems. Because of the dynamic and complex nature of agricultural systems, an integrated approach to N management where both N fertilizer and SOM are considered in crop breeding and system management is an important step in improving agricultural sustainability.
Keywords: agroecology